Fair rail business entity in Indonesia: Challenges and current developments - Anggriani, Reni; Priyono, FX. Joko; Hastuti, Nanik Tri (Kasetsart Journal of Social Sciences, 2023)
The development of railway transportation has experienced growth, namely with the existence of law concerning Railways. The government encourages the government’s contribution and opens up opportunities for business entities to serve the needs of services for rail transportation, which is expected to provide justice for the people who use rail transportation. The research aims to analyze the challenges and developments in the railway business in Indonesia and see whether the railway business entity is fair. The research method is normative legal research, which uses a statute approach. The result shows that the characteristics of railway business entities that are to be involved in railway operations have been regulated in Law (Limited Liability Companies, 2007), especially Article 1 number 10 on Business Entities. This arrangement has ended the monopoly of rail transport providers. This means that engagement opportunities have been opened to participate in the role of all business entities that meet the requirements to serve people in rail transportation mode. In addition, it creates healthy competition in rail transportation. Therefore, fairness can be obtained for the community. This research recommends that it is necessary to create a further explanation and implementation related to the requirements that need to be fulfilled to become a railway operator so there is competition between the existing operator.